Global Ballistic Missile Defense and Strategy of Zero Growth vs. Necessity of Global Cooperation for Sustainable Development - Michnowski, Lesław (Problemy Ekorozwoju, 2023)
The construction of a global defense system by highly developed communities against the threat from communities still guided by egoistic axiology should be preceded by recognizing ecohumanism as the basis for their actions to overcome the global crisis and undertaking the construction of information bases for the politics and economy of the sustainable development of the world community.